Habitat use by a mixed feeder: impala Aepyceros melampus in a heterogeneous protected area. (21st November 2018) - Mandinyenya, Bob; Monks, Norman; Mundy, Peter J.; Sebata, Allan; Chirima, Albert
Abstract: Although large herbivore habitat use has been extensively studied, more information is still required on the use of heterogeneous vegetation types. Over 3 y we carried out monthly road transects in the Zambezi National Park (ZNP), Zimbabwe, to determine the impala density in each of five vegetation types. In addition we determined grass and browse chemical composition to test if at the time the impala switches from grass to browse, grass nutritive quality had declined below that of browse. Furthermore, grass height was measured in the five vegetation types. The impala used mixed, acacia and terminalia vegetation types, which constituted 37% of the protected area and avoided grassland and the predominant Zambezi teak (60% of ZNP) vegetation types. At the time of the diet switch by the impala from grass to browse, woody plant leaf nutritive quality was higher than grass in terms of nitrogen, calcium and acid detergent fibre content. The three vegetation types used by the impala had short to medium grass height. We concluded that when the impala switched from grass to browse the grass nutritive quality was lower than that of the browse.